2021
DOI: 10.1101/2021.03.26.437227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond fish eDNA metabarcoding: Field replicates disproportionately improve the detection of stream associated vertebrate species

Abstract: Fast, reliable, and comprehensive biodiversity monitoring data are needed for environmental decision making and management. Recent work on fish environmental DNA (eDNA) metabarcoding shows that aquatic diversity can be captured fast, reliably, and non-invasively at moderate costs. Because water in a catchment flows to the lowest point in the landscape, often a stream, it can often collect traces of terrestrial species via surface or subsurface runoff along its way or when specimens come into direct contact wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted April 28, 2021. ; https://doi.org/10.1101/2021.04.27.441610 doi: bioRxiv preprint replicates taken within a small geographic area for eDNA-based monitoring of mammals (Figs 1 and 2; Macher et al, 2021). A total of eight species were detected in only one or two locations (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted April 28, 2021. ; https://doi.org/10.1101/2021.04.27.441610 doi: bioRxiv preprint replicates taken within a small geographic area for eDNA-based monitoring of mammals (Figs 1 and 2; Macher et al, 2021). A total of eight species were detected in only one or two locations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…McDevitt et al, 2019;Valentini et al, 2016). However, recent studies have demonstrated that eDNA retrieved from water from both lotic (Sales, McKenzie et al, 2020;Sales, Kaizer et al, 2020;Lozano & Caballero, 2021;Macher et al, 2021;Mariani et al, 2021) and lentic (Ushio et al, 2017;Harper et al, 2019) systems can detect components of the overall terrestrial and semi-aquatic mammalian community.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, the information included in the non-target part of the dataset obtained might provide valuable information about the surrounding ecosystem. More and more studies indicate the significance and validity of information contained in so-called bycatch derived from aquatic eDNA data (Macher et al 2021b; Mariani et al 2021). Thus, including and sharing the entire eDNA sequence dataset could be of paramount importance for further studies from the region and effort should be made towards their storage and public availability (Berry et al 2020; Makiola et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the information included in the non-target part of the dataset might provide valuable information about the surrounding ecosystem. More and more studies indicate the significance and validity of information contained in so-called bycatch derived from aquatic eDNA data (Macher et al, 2021b;Mariani et al, 2021). Thus, including and sharing the entire eDNA sequence dataset could be of paramount importance for further studies from the region and effort should be made towards their storage and public availability (Berry et al, 2020;Makiola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%